On the Interaction of Gestural and Linguistic Perspective Taking - Hinterwimmer, Stefan; Patil, Umesh; Ebert, Cornelia (Frontiers in Communication, 2021)
In this paper, we investigate the question of whether and how perspective taking at the linguistic level interacts with perspective taking at the level of co-speech gestures. In an experimental rating study, we compared test items clearly expressing the perspective of an individual participating in the event described by the sentence with test items which clearly express the speaker’s or narrator’s perspective. Each test item was videotaped in two different versions: In one version, the speaker performed a co-speech gesture in which she enacted the event described by the sentence from a participant’s point of view (i.e. with a character viewpoint gesture). In the other version she performed a co-speech gesture depicting the event described by the sentence as if it was observed from a distance (i.e. with an observer viewpoint gesture). Both versions of each test item were shown to participants who then had to decide which of the two versions they find more natural. Based on the experimental results we argue that while there is no general need for perspective taking on the linguistic level to be aligned with perspective taking on the gestural level, there is both a weak preference for perspective alignment and a preference for the more informative gesture.